Assessing Dysfunctional Expectations in Posttraumatic Stress Disorder: Development and Validation of the Posttraumatic Expectations Scale (PTES). (June 2023) - Herzog, Philipp; Kaiser, Tim; Rief, Winfried; Brakemeier, Eva-Lotta; Kube, Tobias
Dysfunctional expectations are a particularly important subset of cognitions that influence the development and maintenance of various mental disorders. This study aimed to develop and validate a scale to assess dysfunctional expectations in posttraumatic stress disorder (PTSD), the "Posttraumatic Expectations Scale" (PTES). In a cross-sectional study, 70 PTSD patients completed the PTES, the Posttraumatic Cognitions Inventory (PTCI), as well as measures of the severity of symptoms of PTSD and depression. The results show that the PTES has excellent internal consistency and correlates significantly with the PTCI and PTSD symptom severity. A regression analysis revealed that the PTES explained variance of PTSD symptom severity above the PTCI, supporting the incremental validity of the PTES. While the original version of the PTES comprises 81 items, short scales were constructed using the BISCUIT (best items scales that are cross-validated, unit-weighted, informative and transparent) method. The current findings provide preliminary psychometric evidence suggesting that the PTES is an internally consistent and valid novel self-report measure in patients with PTSD. However, conclusions about the psychometric properties of the PTES are limited because of the absence of criterion-related validity, factor structure evidence, variability over time/response to intervention, and test–retest reliability. Future research should use the PTES in large-scale longitudinal studies to address these aspects to further validate the scale.